Sistem Analisa Tingkat Kepuasan Mahasiswa Terhadap Kegiatan Belajar Mengajar pada PSTI Unram dengan Menggunakan Metode Service Quality - Zakiyah Rahmiati; I Gede Pasek Suta Wijaya; Budi Irmawati (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
This system designed by website-based with service quality method which providing display online questionnaire that can be access by students of PSTI Unram. Students objectively fill the questionnaire, then the result will be displayed on page of Head Master, Lecturer and Operator PSTI Unram. There three ways in testing the application, Black Box, System, and Mean Opinion Score. Black Box shows that all the features run well. System shows the result of the system servqual score calculation is accordance with manual calculation. MOS administred 40 respondence of PSTI Unram Students, the result as much as 4,15. This shows that the system has been done well and accordance with the expected. Concluded that with this system, studens able to give the evaluation towards service provided during teaching and learning process, and PSTI Unram can receive the information about the analysis result of students satisfaction level towards the quality of service given. And for PSTI Unram can improve performance to provide an excellent services in the future.